TINGKAT KEBERHASILAN PENDAMPINGAN ABH DALAM UPAYA DIVERSI TAHUN 2018-2020 OLEH PEMBIMBING KEMASYARAKATAN PADA BAPAS BENGKULU - Imran Hasyim (UNIB Press, 2022)
ABSTRACT As the spirit of the birth of Law Number 11 of 2012 concerning the Criminal Justice System for Children. Diversion as an effort to deal with the problem of Children with Legal Problems becomes a challenge for the Community Guidance in the Class II Penitentiary Bengkulu in realizing it. Since its promulgation in 2012, this effort has been carried out in every Children with Legal Problems in Bengkulu Province. It's just that in encouraging the efforts of this Diversion is not optimal because Bengkulu Bapas PK cannot be alone, and must collaborate with other Law Enforcement Officials, such as Police, Prosecutors and Judges. Therefore, the purpose of this study is to measure the success rate of Community Assistance for Community Facilitation in Class II Penitentiary Bengkulu in diversion efforts over the past three years. The method used in this research is quantitative research. With a descriptive analysis method to the trend of the number of cases of Children with Legal Problems assistance by Community Guidance in the Class II Penitentiary Bengkulu Diversified. From 2018, 2019 and 2020 it can be seen that the movement of the comparison of the number of assistance from Children with Legal Problems is sought by Diversi every year to increase. And Children with Legal Problems cases that went to trial at the District Court experienced a decline. This trend could be due to the maximum efforts of the Community Facilitation in Class II Penitentiary Bengkulu who at each stage of assistance paid close attention to each of the best rights for Children with Legal Problems. Keywords: Children; Diversion; Guidance